2013
DOI: 10.5811/westjem.2013.4.14296
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Capnography for Suspected Diabetic Ketoacidosis in the Emergency Department

Abstract: Introduction:Metabolic acidosis confirmed by arterial blood gas (ABG) analysis is one of the diagnostic criteria for diabetic ketoacidosis (DKA). Given the direct relationship between end-tidal carbon dioxide (ETCO2), arterial carbon dioxide (PaCO2), and metabolic acidosis, measuring ETCO2 may serve as a surrogate for ABG in the assessment of possible DKA. The current study focuses on the predictive value of capnography in diagnosing DKA in patients referring to the emergency department (ED) with increased blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 13 publications
(16 reference statements)
2
37
0
Order By: Relevance
“…Palma de Mallorca, IB, Spain, 2016AuthornCannula usedType of sensor Capnograph usedMeasurement durationPishbin et al ( 1 ) 64Nc*SidestreamCapnocheck (r) Sleep Capnograp/oximeter.NK/NA † Agus et al ( 11 ) 72Nc*MicrostreamMDE Escort Prism (r) monitorNK/NA † Gilhotra & Porter ( 23 ) 58Nc*SidestreamPhilips M3046A.1 minSolana et al ( 12 ) 25Nco ‡ MicrostreamPhilips smarth capnoline O2 pediatrics.30 sec-1minNagler et al ( 24 ) 130Nco ‡ MicrostreamMicrocap; Oridion.1-2 minKartal et al ( 29 ) 240O § SidestreamMedlab Cap 10 sidestream.NK/NA † McGillicuddy et al ( 30 ) 97NK/NA † MicrostreamNelcor NBP-70.NK/NA † Soleimanpour et al ( …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Palma de Mallorca, IB, Spain, 2016AuthornCannula usedType of sensor Capnograph usedMeasurement durationPishbin et al ( 1 ) 64Nc*SidestreamCapnocheck (r) Sleep Capnograp/oximeter.NK/NA † Agus et al ( 11 ) 72Nc*MicrostreamMDE Escort Prism (r) monitorNK/NA † Gilhotra & Porter ( 23 ) 58Nc*SidestreamPhilips M3046A.1 minSolana et al ( 12 ) 25Nco ‡ MicrostreamPhilips smarth capnoline O2 pediatrics.30 sec-1minNagler et al ( 24 ) 130Nco ‡ MicrostreamMicrocap; Oridion.1-2 minKartal et al ( 29 ) 240O § SidestreamMedlab Cap 10 sidestream.NK/NA † McGillicuddy et al ( 30 ) 97NK/NA † MicrostreamNelcor NBP-70.NK/NA † Soleimanpour et al ( …”
Section: Resultsmentioning
confidence: 99%
“…Among those studies focused directly on metabolic changes, it was found a study 3 that is the only one aiming at the detection of DKA in adults. In such a study, it was obtained a moderate correlation between EtCO 2 and PaCO 2 (0.572, p>0.0001) and a strong correlation between EtCO 2 and HCO 3 ¯ (r=0.730, p>0.0001), indicating that values of EtCO 2 > 24.5mmHg were out of the interval for DKA, with sensitivity of 0.90 and specificity of 0.90.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate lung sliding, linear probe was placed on anterior chest in midclavicular line in both hemithorax, and lung movement across parietal pleura was seen as slipping. The results of intubation were confirmed or rejected by capnography (18). The results were analysed by SPSS Version 17.01 (SPSS Inc., Chicago, Illinois).…”
Section: Methodsmentioning
confidence: 95%
“…Currently, capnography is used to evaluate ventilation in clinical wards. Capnography produces the a value for end tidal carbon dioxide (ETCO 2 ) and can precisely monitor a patient’s ventilation status (9, 10). Given the above, it appears that use of a ventilation monitor in multiple trauma patients, especially with a neck collar, is necessary.…”
Section: Introductionmentioning
confidence: 99%